Identifying Occupational Stress and Coping Strategies 2023
DOI: 10.5772/intechopen.109148
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress-Related Sleep Anomaly in Frontline COVID-19 Health Workers: The Possible Underlying Mechanisms

Abstract: COVID-19 is a highly contagious viral illness that has claimed millions of lives worldwide. Since its emergence, it has exerted a negative impact on many sectors globally without the exception of frontline COVID-19 healthcare providers. Specifically, in frontline COVID-19 healthcare workers, occupational stress-related sleep disorders such as insomnia and daytime somnolence have been extensively reported and were characterized by neuro-immunological changes. However, the possible mechanisms that underlie the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 120 publications
0
2
0
Order By: Relevance
“…Peripheral oxygen saturation and shock index indicate level of tissue perfusion. Peripheral oxygen saturation is a proportion of oxygenated blood and it is influenced by capillary density [21,[36][37][38][39][40]. The study showed that post-exercise orthostasis elicited a decrease in peripheral oxygen saturation in males when compared to females.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral oxygen saturation and shock index indicate level of tissue perfusion. Peripheral oxygen saturation is a proportion of oxygenated blood and it is influenced by capillary density [21,[36][37][38][39][40]. The study showed that post-exercise orthostasis elicited a decrease in peripheral oxygen saturation in males when compared to females.…”
Section: Discussionmentioning
confidence: 99%
“…It can also disrupt circadian rhythms, causing deranged melatonin secretion, altered leptin secretion, impaired hormonal secretions and altered sleep/wakefulness cycle [44][45][46][47]. Noise can cause headache, confusion, increase in blood pressure and heart rate [3,17,[48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%